الشفاعة المحمدية وأداتها من الأحاديث - Suriati Bt Yusof; سورياتي بنت يوسف (Universiti Sains Islam Malaysia, 2022)
The study project aims to discuss about the topic Prophet Muhammad's shafa'at in hereafter, The writer will discuss about definition and types of shafa'at. Shafa'at is an assistance or help from Allah to Muslims in the hereafter. No one will be honored with shafa'at without the permission from Allah. The goal of this study is to how what is shafa'at and what types in shafa'at. Tools that the writer done to complete this study is from library research which gathering information or data based on books. From this information, we can understand what is Prophet Muhammad's shafa'at, what are types of shafa'at and who can get this shafa'at. Therefore, h m this study, as Muslims, we must follow the teaching of our Prophet by doing good deeds, so we can get shafa'at Muhammadiah.